Tinjauan Pengaruh Kondensor Dummy (Tipe Helical Coil, Trombone Coil dan Multi Helical Coil) Terhadap Temperatur Ruangan Dan Temperatur Air Panas - Purba, Adi Hans; Aziz, Azridjal; Mainil, Rahmat Iman (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
This paper provide a review of i.e: temperature achievement three different of dummy condenser. The study review was conducted to know the effect of adding dummy condenser coil type helical, coil trombone and multi helical coil without circulating water to room temperature and the temperature of the hot water. The method used in this review was a comparative method among tree types of dummy condenser i.e: helical coil, trombone coil and multi helical coil. The result comparison showed that the addition of dummy condenser type multi helical coil was better than dummy trombone coil and helical coil types. In the addition of dummy condenser without circulating water with multi helical coil, heated water temperature reached 64.73 oC in 3000 Watt of load. Whilst, the helical coil on the lowest room temperature reached 16.11 oC at the use of no load (19.26 oC on multi helical coil without load).Keywords : Air Conditioning Machines, Dummy Condenser, Cooling Load, Coil, Water Heater.